Is nitrogen-modified atmosphere packaging a tool for retention of volatile terpenes and cannabinoids in stored Cannabis sativa inflorescence? - Luke L. MacLaughlin; Mason T. MacDonald (Journal of Cannabis Research)
Abstract Modified atmosphere packaging (MAP) alters the gaseous composition of air surrounding packaged goods to prevent deleterious oxidation associated reactions. MAP has been adopted for the storage of cannabis, though a recent study revealed little difference in terpene content under MAP conditions. Questions regarding its efficacy for preservation of high value compounds like terpenes and cannabinoids lost during postharvest storage remain. The goal of this research is to determine weather N2 MAP preserves high value compounds of cannabis during its postharvest storage. This experiment followed a completed randomized block design. There were two factors of interest. The first was storage atmosphere (atmospheric or N2 MAP). The second was storage duration (18, 46, or 74 days). The experiment was then blocked by cannabis chemovar using 5 different chemovars. The concentration of 17 cannabinoids was evaluated through UPLC-UV and 61 volatile terpene compounds through GC–MS. Concentrations were compared over time and between storage treatments. There were no significant differences in total cannabinoids and volatile terpene compounds over time or between storage treatments. Individual cannabinoids Δ9-THC, CBG, CBNA, CBC, THCV, and THCVA all increased during storage time while THCA decreased. CBG and THCV only increased under MAP storage. Individual aromatics limonene, β-pinene, α-pinene, camphene, and terpinolene all only decreased during storage under N2 MAP. Only caryophyllene oxide and α-humulene increased under N2 MAP storage. β-Myrcene decreased under atmospheric storage, but not under N2 MAP. While N2 MAP had no effect on the preservation of total cannabinoids and aromatics during storage, it did influence several individual compounds. CBG, THCV, and α-humulene all increased under N2 MAP. N2 MAP also maintained the concentration β-myrcene over time, though the preservation of β-myrcene was offset by a decrease limonene. Overall, N2 MAP was not needed for preservation of most high value compounds but did have an effect of some compounds with reputed therapeutic benefits.